PERBEDAAN HASIL BELAJAR SISWA SMA NEGERI 5 PALU MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COURSE REVIEW HORAY DAN KONVENSIONAL PADA MATERI LARUTAN ELEKTROLIT DAN NONELEKTROLIT - Salim, Agustiawan Amat; Said, Irwan; Gonggo, Siang Tandi (Universitas Tadulako, 2013)
One of indicator that quality of education said to be good is when students able to apply what they have learned at school to deal with problems in their daily life. Learning in the classroom should not only focus on mastery of the materials but also how to create the atmosphereT in the classroom to be fun and interesting so that students are not bored and learning outcomes can be improved. Course Review Horay (CRH) is one of a model that can be applied. This research aims to find out the difference of learning outcome of SMA Negeri 5 Palu through cooperative learning model application of CRH on electrolyte and non electrolyte solutions material. Populations of this research are all students of grade X of SMA Negeri 5 Palu for Academic Year of 2012/2013 which are consists of seven classes. Sample of this research consist of two classes which are class XA with 28 students as experiment class and class XG with 27 students as control class which determined by purposive sampling. Data collection is conducted using test instrument such as chemistry learning achievement of Electrolyte and non electrolyte solutions material. Data from research result is tested using two parties t-test with prerequisite test which are; normality test and homogeneity test. Average score of students learning outcome using cooperative learning model CRH is 23.21 while the average score of students learning outcome who join the conventional teaching is 19.93. Based on the statistic analysis with statistic t-test is achieved thitung = 4.81 and this is in the rejection area of H0 which is -2.00 and 2.00. Therfore, it can be concluded that there is a difference of students learning outcome through Cooperative learning model application of CRH type and conventional to the students grade X of SMA Negeri 5 Palu.